Status of stress among the attendes attending the patient in the selected hospital in Katmandu valley. - Shakya, Tridendra (2012)
ABSTRACT: The aim of the study was to the level of stress in patient attendees during the course of attendance with patient. A descriptive cross sectional study design was used. Attendees attending severely ill hospital admitted patient were included and out-patients were excluded from the study. Stress was assessed on 5 attendees of the patients from selected hospital. The tools used were Structured Performa (for recording socio-demographic details,) and Hospital Anxiety and Depression Scale (HADS), General Stress Test (GST), Coping Strategy Scale (CSS), Stress Resiliency Scale (SRS), Cumulative Stressor Checklist (CSC). The mean level of stress in attendees attending the patient were seen higher in patient admitted in general ward with no family support. Moderate level of stress exists among attendees attending the patient admitted to single special ward Key words: Stress, Attendees, GST, HADS, CSS. SRS, CSC.